„Scara lui Iacob“ și rostirea scenică - Alb, Dan (Theatrical Research, 2021)
Jacob’s Ladder and Scenic Discourse Artistic creation (dramatic creation, by choice) restores a path between the everyday life and the celestial one, owing to the fact that it is caught between manifestations of the material and those of the ephemeral. Dramatic creation actually wears itself to a shadow while it ascends and descends “Jacob’s Ladder”, with backwards-and-forward movements. Thus, the theatre itself acquires a “theurgic” particularity as it magically materializes aspects of the spiritual world. On the one hand, it appeals to the discourse of the imaginary and, on the other hand, it calls down its shapes, which, according to Henry Corbin, could be seen within a utopian world that resides outside the human being.